2004
DOI: 10.1097/01.inf.0000109289.55856.27
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of a three dose regimen of two tetravalent live-attenuated dengue vaccines in five- to twelve-year-old Thai children

Abstract: Dengue fever, caused by four serotypes of a mosquito-borne virus, is a growing problem in tropical countries. Currently, there is no treatment or vaccine. We evaluated safety and immunogenicity of two doses, given six months apart, of seven formulations of dengue tetravalent live-attenuated vaccine (containing different concentrations of the component viruses) versus placebo in 59 flavivirus-seronegative Thai adults. The first dose was the more reac-togenic. Most volunteers experienced clinically moderate feve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
84
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(84 citation statements)
references
References 17 publications
0
84
0
Order By: Relevance
“…A major problem with previously evaluated TVs has been their capacity to cause a DEN-like illness in vaccinees (11,26,38). This reactogenicity appears to be related to a high level of replication of at least one of the components of the TV.…”
Section: Discussionmentioning
confidence: 99%
“…A major problem with previously evaluated TVs has been their capacity to cause a DEN-like illness in vaccinees (11,26,38). This reactogenicity appears to be related to a high level of replication of at least one of the components of the TV.…”
Section: Discussionmentioning
confidence: 99%
“…Initial immunogenicity data of live-attenuated dengue vaccines among persons with no previous DENV exposure shows that 3 doses are required over a 12 month period. 23 Such a schedule would limit use of this vaccine to highly selected populations of overseas workers, frequent travelers, or the military. Studies have shown that the majority of travelers seek pre-travel health advice less than 1 month before departure which makes a vaccine with 6 or even 12 months dose spacing difficult in this population.…”
Section: Discussionmentioning
confidence: 99%
“…DNA vaccines consisting of plasmids expressing one or a few proteins from each DENV serotype are in an earlier stage of development, as are subunit vaccines based on purified recombinant DENV proteins (23,24). Several of these approaches have demonstrated protective efficacy in animal models of DENV infection, and a few have shown safety and immunogenicity in early phase clinical studies (14,18,25,26).…”
mentioning
confidence: 99%